CircCCT3 Enhances Invasion and Epithelial-Mesenchymal Transition (EMT) of Non-Small-Cell Lung Cancer (NSCLC) via the miR-107/Wnt/FGF7 Axis. (22nd June 2022) - Li, Jinyou; Lu, Rongguo; Yang, Kejia; Sun, Qi
Abstract : Background . CircRNAs play a role in a variety of biological processes, including tumorigenesis. circCCT3 has been shown to regulate cancer initiation and progression. Unfortunately, whether circCCT3 is involved in non-small-cell lung cancer (NSCLC) metastasis remains unclear. Methods . Our study utilized RT-qPCR to examine gene expression levels. A transwell assay was used to measure invasion ability of cells. Starbase software and TargetScan software were used to predict target genes. Results . circCCT3 knockdown attenuated invasion and epithelial-mesenchymal transition (EMT) of A549 and Calu-1 cells. miR-107 mimics could rescue circCCT3-induced invasion and EMT. Next, miR-107 mimics and circCCT3 knockdown suppressed Wnt3a and FGF7 expression. An miR-107 inhibitor promoted Wnt3a and FGF7 expressions. Finally, FGF7 greatly restored miR-107-inhibited invasion and EMT of A549 cells. Conclusion . Here, we reveal a molecular mechanism circCCT3/miR-107/Wnt/FGF7 responsible for NSCLC metastasis.